A methodology for implementation of the mechanistic-empirical rigid pavement design in Turkey - Shakhan, Mohammad Razeq; Topal, Ali; Şengöz, Burak (Fırat University, 2021)
The Mechanistic-Empirical Pavement Design Guide (MEPDG) was emerged and calibrated based on the North American conditions for analysis and designing of flexible and rigid pavements. Implementing this guide in elsewhere needs evaluation using local data, if need be, the local calibration should be conducted to improve the accuracy of the pavement distress prediction models. State agencies and countries have followed different implementation methodologies to adopt the method. In this study, a methodology was developed for the implementation of the ME Rigid Pavement Design Guide in Turkey. This methodology can serve as a guide for local calibration of the MEPDG in Turkey as well as countries.
Keywords: Engineering; Mühendislik